The Influence of Audit Committee and Intellectual Capital on Company Value: The Role of Company Performance - Fitri, Winky Trisiya; Meini, Zumratul (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2023)
The era of globalization has greatly influenced the development of the business world because it has proven to increase competition. This condition triggers the company to be able to continue to compete in order to obtain good value and perceptions from shareholders. This study aims to empirically prove the influence of audit committees and intellectual Capital on firm value. The novelty of this study is to test whether financial performance can mediate the influence of audit committees and intellectual Capital on firm value. The data used in this study are 80 companies in the consumer goods industry sector listed on the Indonesia Stock Exchange during the 2017-2021 period. Data processing was carried out using SPSS Version 26. The results showed that the Audit Committee had no significant effect on Financial Performance, Intellectual Capital had a significant positive effect on Financial Performance, Financial Performance had a direct effect on Firm Value, Audit Committee had no direct effect on Firm Value, Intellectual Capital had an effect directly on Firm Value, the Audit Committee has no indirect effect on Firm Value through Financial Performance, and Intellectual Capital has an indirect effect on Firm Value through Financial Performance. The results of this study have implications for companies to pay attention to the application of Intellectual Capital and to further improve the effectiveness of corporate governance through the performance of the Audit Committee.